Estado da Arte da Residência Multiprofissional em Saúde no Brasil - Lais Santos Silva; Sônia Natal; Luise Ludke Dolny (UniEVANGÉLICA, 2018)
Objective: To identify the limitations and facilitators of Multiprofessional Residences in Brazil. Data source: In order to operationalize the study, we used the integrative review in the Scientific Electronic Library Online (SCIELO), Virtual Health Library (VHL) and Latin American and Caribbean Health Science Literature (LILACS) databases, from March and April 2017, from the descriptors "Evaluation and residence and multiprofessional", "Residence and health and education and permanent" and "Residence and multiprofessional". Data synthesis:The findings corroborate the limiting factors of the programs, such as the difficulty of partnerships between educational institutions and health services network, the low interaction of the participating actors, the primary and specific training of professionals. As potential elements, there is an opportunity to acquire knowledge,to train qualified professionals and to increase the relationship between theory and practice in the learning spaces. Conclusions:The selected articles demonstrated the challenges of residency implantation and its consolidation from two paradoxes: the program represents an important tool for training professionals for SUS, but, on the other hand, considered a form of precariousness of work.